Aspek Kapital dalam Teo-estetis Wayang Kalpataru (Studi Wayang JDR Bali) - I Made Danu tirta (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Kalpataru puppets belonging to the JDR Puppet Team Bali have characteristics in the form of internalization of the capital aspect,which has not been found in other puppets. Evidently, many pictures with capital nuances adorn Kalpataru puppets. In narrative, this writing tries to analyze the elements and meanings of capital in Kalpataru puppets. The elements of capital in the Kalpataru puppetscan be observed through the pouring of images or capital symbols such as money, gold, land, rice and milk on the physical puppets.The capital element in the relationship with Kalpataru puppets is shown by the placement of Kalpataru puppets (along with the capital aspect) as a sign of heaven in every play.The capital element in the Kalpataru puppetsperformance was expressed through the emphasis on capital-filled dialogue by Punangkawan(Tualen) when Kalpataru puppetswas performed.The capital aspect of Kalpataru puppets means liberation of the soul or a runway (tool) in achieving the highest goal of Hinduism namely, Moksartham Jagadhitaya Ca Iti Dharma.The Kalpatru puppet is expected to become an artistic aspect that educates the wisdom of utilizing capital in the lives of Hindus.